Study of the effectiveness of comprehensive, timely, and family-oriented interventions in reducing the symptoms of autism in children - Katayoon Razjouyan (Journal of Family Medicine and Primary Care, 2020)
Background and Objectives: The onset of rehabilitation interventions in children with autism spectrum disorder below 5 years old has been associated with the reduction of autism symptoms in all developmental domains. The present study aimed to illustrate the importance of early family-oriented interventions in the reduction of the problems and symptoms of children with autism spectrum disorder. Methodology: This study was a pretest-posttest clinical trial without a control group. Fifty patients were selected using a convenience sampling method, of which forty patients were male and 10 females with a mean age of 3.2 ± 1.4. The efficacy assessment was evaluated using the Autism Behavior Checklist (ABC) and the Autism Treatment Evaluation Checklist (ATEC) as pretest and posttest. Data were analyzed by independent T-test using SPSS software. Results: The difference between pretest and posttest was significant in all aspects of the ATEC test (communication, health, sensory and cognitive awareness, socialization) at the level of P < 0.001. Moreover, the difference between pretest and posttest was significant at P < 0.001 for the aspects of speech, social and communication, and general performance, and at P < 0.002 for the sensory processing. Conclusion: Timely interventions under 6 years old with an emphasis on family-oriented and growth aspects over one year can help autistic children in the aspects of speech, social and communication, sensory processing, and sensory and cognitive awareness.